Implementation of Home Parenting Activities as an Effort to Prepare Early Childhood Growth and Development - irchamni, Achmad; Anwar, Sholihul; Utami, Daya (Indonesian Journal of Early Childhood Education Studies, 2023)
Parents have an essential role in caring for, educating, and meeting the needs of a child, especially in the aspect of growth and development. How parents educate is very important for the growth and development of early childhood. Education and upbringing at home must be harmonized with education at school so that children grow up to be intelligent, independent, and have character, growing into strong and rugged individuals. This research was motivated by a need for parental awareness of children's learning activities at school, inappropriate parenting patterns, and the importance of children's education. This research aims to determine children's development as a communication tool and the model for implementing learning programs in collaboration with parents in early childhood education, especially in Blora Regency. This research was conducted using a qualitative approach obtained through interviews, documentation data, and observation data regarding the implementation of home parenting programs or activities. This research shows that home parenting activities can be carried out through reporting on children's learning progress at school, knowledge of early detection of growth and development, parents' skills in creating work, and involvement of parents as resource persons. Parenting methods are usually carried out at school and sometimes only once a semester; for home parenting, this is done once a month. Implementing home parenting activities can make it easier for parents to provide parenting lessons and learn more about their children's activities.